Green Economy / Green Revolution: an ecolinguistic critical discourse analysis of South African political parties' public communications on climate change. - Laurie, Julia (Linguistics, 2023)
The intertwined planetary crises of anthropogenic climate change and ecological degradation have already begun, and the effects are being felt around the world (IPCC, 2022, World Meteorological Organisation, 2021). However, it is still not being treated as a crisis by global policymakers or the media. Although Africa contributes only 4% of global greenhouse gas emissions, the continent is the most vulnerable to the impacts of the climate crisis. At the same time, South Africa is an outlier to the rest of Africa, being the 12th highest greenhouse gas emitter worldwide (Global Carbon Atlas, 2020). This is due in large part to South Africa's reliance on coal, both as the centre of the country's export economy and as a source of energy at home. However, South African policymakers have yet to take any significant climate change mitigation actions. This is the central social and ecological problem that serves as impetus for this study. This study investigates the climate change-related communications of South Africa's three major political parties, namely the ANC, the DA, and the EFF, from a critical perspective. It explores a wide variety of public political discourse genres in which the topic of climate change is mentioned. Utilising an ecolinguistic and critical discourse analytic framework, this study aims to uncover the “stories” (Stibbe, 2015:6) South African political parties are telling about climate change. Drawing on Fairclough's (1989) three stage approach to analysis, as well as tools from corpus linguistics and the emerging field of ecolinguistics (Stibbe, 2015), it examines both broad quantitative patterns across the data and specific instances of discourse in detail. In particular, the discursive strategies of naturalization, framing, and erasure and salience patterns are investigated. As a CDA study, the focus is on making visible the messages that are implicit in discourse, particularly those in service of power. As an ecolinguistic study, the focus is on the potential ecologically damaging impacts of these messages. Using the above analytical tools, this study shows the political parties' climate change communications to be sites of discursive conflict. It illustrates the ways all three parties, but particularly the ANC and DA, continuously undermine their ostensible commitment to combating the climate crisis with discourses that “tame” it and evade responsibility for addressing it. This is done through framing climate change as an economic issue and as an opportunity for technological innovation and entrepreneurship, through telling the story that individual actions are key to solving climate change, through naturalizing current levels of carbon emissions, and through presenting climate change as “manageable”. In addition, all three parties construct the natural world as existing for the benefit of humans. While the EFF does not exhibit the above taming discourses to the same extent, their dominant climate change story is one of erasure through the absence of discussion. Thus, all three parties naturalize the continued destruction of the planet's life support systems and obscure the central causes of this destruction